Etika dan Tanggung Jawab Profesi Akuntan dalam Pelaporan Keuangan Perusahaan - Daariin Dewi Nabiilah; Safira Permata Kristia Putri; Tries Ellia Sandari (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The purpose of this study is to analyze the role of professional accounting ethics in maintaining the quality, transparency, and accountability of corporate financial reporting through a literature review of relevant journals, regulations, and cases, including the Garuda Indonesia case, which illustrates ethical violations in revenue recognition. The findings emphasize that the principles of integrity, objectivity, professional competence, confidentiality, and professional behavior serve as fundamental pillars for accountants in producing reliable financial information. Ethical misconduct can lead to declining public trust, weakened corporate governance, and increased legal and reputational risks. Therefore, ethical education, regulatory supervision, strengthened moral awareness, and effective internal control systems are essential to prevent financial reporting manipulation. Professional more than just an normative obligation but a strategic element in safeguarding the credibility of the accounting profession and ensuring economic stability.